Sex differences in prevalence of electrocardiographic and echocardiographic left ventricular hypertrophy among patients with coronary artery disease. (3rd October 2022) - Haukilahti, M A E; Kentta, T V; Kiviniemi, A M; Tulppo, M; Lepojarvi, E S; Piira, O P; Perkiomaki, J S; Junttila, M J; Huikuri, H V
Abstract: Background: Both electrocardiographic left ventricular hypertrophy (ECG-LVH) and echocardiographic LVH (echo-LVH) are associated with higher risk of cardiovascular and sudden cardiac death. ECG-LVH seems to be partly distinct from echo-LVH as many subjects with echo-LVH do not have ECG-LVH and vice versa. The difference between sexes have not been studied earlier. Purpose: The aim of this study was to determine sex differences in prevalence of ECG-LVH and echo-LVH among patients with coronary artery disease (CAD) and to study if ECG-LVH would have higher accuracy for echo-LVH in either of sexes. Methods: Standard 12-lead electrocardiograms and echocardiographic measurements were studied from 1, 894 subjects of ARTEMIS Study (31.8% women). Echo-LVH was determined as estimated left ventricular (LV) mass ≥201 g in men and ≥151 g in women and was categorized as mildly, moderately and severely abnormal. ECG-LVH was determined if either criteria of Sokolow-Lyon or Cornell were met. Results: Echo-LVH was found from 1, 162 of the study subjects (women 34.3%, p=0.004) and ECG-LVH only from 222 of the subjects (women 55.9%, p<0.001). Of those with ECG-LVH, 82.0% had increased LV mass (p<0.001), and ECG-LVH seemed to correlate slightly better to echo-LVH in women than in men (82.3% vs. 81.6%, p<0.001). Of those with ECG-LVH, 47.7% had severe echo-LVH (p<0.001). The prevalence of ECG-LVH was the higher the greater the LV mass was. Among men with ECG-LVH, 46.9% had severe echo-LVH (p<0.001). Among women with ECG-LVH, 16.1% had mild echo-LVH (p=0.029) and 48.4% severe echo-LVH (p<0.001). In addition, 18% of those with ECG-LVH did not have echo-LVH (p<0.001). This proportion was slightly smaller in women than in men (17.7% vs. 18.4%, p<0.001). Only 15.7% of the subjects with echo-LVH had ECG-LVH (p<0.001). This proportion was significantly higher in women than in men (25.6% vs. 10.5%, p<0.001). ECG-LVH was more common finding in subjects with severe echo-LVH as 20.9% of those CAD patients had ECG-LVH (p<0.001). Among women with severe echo-LVH, ECG-LVH was found in 35.3% (p<0.001) whereas only in 13.7% of men with severe echo-LVH (p<0.001). The prevalence of ECG-LVH seemed to be considerably higher among female CAD patients with T2DM and without prior MI as ECG-LVH was seen in 33.0% of those subjects with at least midl echo-LVH (p<0.001) and 43.8% of those subjects with severe echo-LVH (p<0.001). In male patients from similar subgroup and some degree of echo-LVH, ECG-LVH was seen in 6.7% (p=0.042) and with severe echo-LVH in 12.2% (p<0.001) of the subjects. Conclusions: In patients with CAD echo-LVH was often seen without signs of ECG-LVH, especially in men. Majority of the CAD patients with ECG-LVH had also echo-LVH and the prevalence on ECG-LVH was the higher the greater the LV mass was. ECG-LVH seemed to correlate better to anatomic LVH in women with CAD than in men, and the sex difference was highlighted in CAD patients with T2DM and no prior MI. Funding Acknowledgement: Type of funding sources: None.